2018
DOI: 10.1002/adsc.201801482
|View full text |Cite
|
Sign up to set email alerts
|

Access to CF3‐Containing Cyclopentaquinolinone Derivatives from Indolyl‐ynones via Silver‐Catalyzed One‐pot Reaction

Abstract: An unexpected Ag(I)-catalyzed cascade reaction between substituted indolyl-ynone and Togni's reagent has been disclosed in which multiple processes occur including indole dearomatization, ring expansion, trifluoro-methylation and dehydrogenation. This one-pot reaction can be used to conveniently access diverse CF 3 -containing multisubstituted cyclopentaquinolinone scaffolds in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
(23 reference statements)
1
21
0
Order By: Relevance
“… 3 6 For example, our groups and others have shown that the activation of the alkyne moiety of 1 promotes efficient dearomatizing spirocyclization 7 , 8 to form medicinally important spirocyclic indolenines 2 ; 9 , 10 this is most commonly done using π-acidic catalysts (especially Ag(I) species), although Brønsted acids, palladium(II) complexes, and electrophilic halogenation reagents can also be used ( 1 → 2 , Scheme 1 a, step 1). 3 , 11 , 12 Our groups have also shown that dearomatization works well on 2-halogenated indoles (i.e., 1 where X = Cl, Br or I) and that the resulting indoleninyl halide products (i.e., 2 where X = Cl, Br or I) can be transformed further via reaction with nucleophiles, or via Pd-catalyzed cross-coupling, to substitute the halide for various other groups ( 2 → 3 , Scheme 1 a, step 2). 5 Finally, our groups and others have demonstrated that spirocyclic indolenines of the form 3 will rearrange via a one-atom ring expansion reaction 13 to form annulated quinolines, with both acidic and basic reagents able to promote this transformation ( 3 → 4 , Scheme 1 a, step 3).…”
mentioning
confidence: 99%
“… 3 6 For example, our groups and others have shown that the activation of the alkyne moiety of 1 promotes efficient dearomatizing spirocyclization 7 , 8 to form medicinally important spirocyclic indolenines 2 ; 9 , 10 this is most commonly done using π-acidic catalysts (especially Ag(I) species), although Brønsted acids, palladium(II) complexes, and electrophilic halogenation reagents can also be used ( 1 → 2 , Scheme 1 a, step 1). 3 , 11 , 12 Our groups have also shown that dearomatization works well on 2-halogenated indoles (i.e., 1 where X = Cl, Br or I) and that the resulting indoleninyl halide products (i.e., 2 where X = Cl, Br or I) can be transformed further via reaction with nucleophiles, or via Pd-catalyzed cross-coupling, to substitute the halide for various other groups ( 2 → 3 , Scheme 1 a, step 2). 5 Finally, our groups and others have demonstrated that spirocyclic indolenines of the form 3 will rearrange via a one-atom ring expansion reaction 13 to form annulated quinolines, with both acidic and basic reagents able to promote this transformation ( 3 → 4 , Scheme 1 a, step 3).…”
mentioning
confidence: 99%
“…The authors proposed broadly the same mechanism as that shown in Scheme b for this metal‐free variant, although again, no evidence was obtained in its support. Most recently, Song, Liu and co‐workers observed a closely related transformation unexpectedly during a silver(I)‐catalysed trifluoromethylation cascade process and the same mechanism was again proposed …”
Section: Introductionmentioning
confidence: 71%
“…To the best of our knowledge, this indolenine to quinoline rearrangement reaction is without precedent outside of these studies , , . Therefore, we believe that more convincingly ascertaining the mechanism of this unusual ring expansion rearrangement reaction is important, and our attempts to do so are reported in this manuscript using a density functional theory (DFT) approach .…”
Section: Introductionmentioning
confidence: 94%
“…[18] Keepingthe reputation of trifluoromethyl group in attention, an easy access to CF 3 bearing heterocyclesb yt ransition metal catalystfrom indolyl ynones was reported by Li and co-workers (Scheme 7). [19] Even though metal catalyzed transformation of indolyl ynones into spiro-indoleninesa nd acid mediated transformationi nto quinolines are well explored by Unsworth group, domino trifluoromethylation was not explored.D earomatizings pirocyclization through the similarm echanism discussed earlier (Scheme 4) followed by addition of trifluoromethyl radical to the reactive intermediate 46 and successive oxidation resulted the trifluoromethylated quinoline 40 in good yield (Scheme 8). Electron donating and withdrawing substitutions on indole found to be wellt oleratedb ut aromatic substituted ynone terminus (except 4-NMe 2 -C 6 H 4 )f ound to be tolerable producing moderate to good yield.…”
Section: Metamorphosis Involving Dearomatizing Spirocyclization Reactmentioning
confidence: 99%